Towards Immersive Mixed Reality Street Play: Understanding Co-located Bodily Play with See-through Head-Mounted Displays in Public Spaces - Hu, Botao Amber; Lin, Rem RunGu; Tao, Yilan Elan; Laato, Samuli; Li, Yue (Association for Computing Machinery, 2026)
As see-through Mixed Reality Head-Mounted Displays (MRHMDs) proliferate, their usage is gradually shifting from controlled, private settings to spontaneous, public contexts. While location-based augmented reality mobile games such as Pokémon GO have been successful, the embodied interaction afforded by MRHMDs moves play beyond phone-based screen-tapping toward co-located, bodily, movement-based play. In anticipation of widespread MRHMD adoption, major technology companies have teased concept videos envisioning urban streets as vast mixed reality playgrounds-imagine Harry Potter-style wizard duels in city streets-which we term Immersive Mixed Reality Street Play (IMRSP). However, few real-world studies examine such scenarios. Through empirical, in-the-wild studies of our research-through-design game probe, Multiplayer Omnipresent Fighting Arena (MOFA), deployed across diverse public venues, we offer initial insights into the social implications, challenges, opportunities, and design recommendations of IMRSP. The MOFA framework, which includes three gameplay modes-''The Training'', ''The Duel'', and ''The Dragon''-is open-sourced at https://github.com/realitydeslab/mofa.